Question Tag Features Used by Female Characters in The To All The Boys Movies - Putri Azizah Meysi Oemardi; Ni Ketut Alit Ida Setianingsih; Ida Ayu Made Puspani (Program Studi Sastra Inggris, Fakultas Ilmu Budaya, Universitas Komputer Indonesia, 2026)
This study entitled Question Tag Features Used by Female Characters in the To All The Boys Movies. The aims of this study are to identify the kinds of question tag features in the women characters and describe the context of the situation of the conversation containing question tags in the To All the Boys movies. The source of the data was taken from the conversation of “To All The Boys” movies. The research design was descriptive qualitative research. The analysis was based on the three-question tag from Holmes’s theory; they are the modal tag to ask for information or confirmation of the information, affective tag to reduce the force of an impolite request, and the facilitative tag to invite the listeners to take a conversation and comment. This data was also analysed based on the context of the situation from Holmes's theory. The result shows that there are thirteen data from the conversation in the movie to perform the question tag. The feature of question tags that occurs dominantly in the movie is a modal tag. The six cases comprise a modal tag of two cases, a facilitative tag of two cases, and a softeners tag of two cases. Meanwhile, for the context of the situation factors that most influence the speaker to use question tags are participant, setting, topic, and function. Based on the result of the study, it is fruitful to suggest the students of English Department to do further analysis about the three of question tags used in other resources like movies, novels, or articles. Keywords: Question Tag, To All the Boys, Movie